The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1016/s0006-3495(88)83166-7
|View full text |Cite
|
Sign up to set email alerts
|

Modal gating behavior of cardiac sodium channels in cell-free membrane patches

Abstract: Single voltage-activated Na+ channel currents were obtained from membrane patches of isolated ventricular cells of guinea pig hearts. The currents were compared when measured from cell-attached patches and from the same patch but at least 20 minutes after manual excision. The averaged currents showed a distinctly delayed decay in the excised patches due to the appearance of long lasting openings or bursts of openings. In contrast to control patches, the open time distribution in excised patches requires at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 19 publications
(15 reference statements)
6
65
0
Order By: Relevance
“…Modal changes in both activation and inactivation kinetics have been reported. The inactivation gating modes found for Na channels (Patlak and Ortiz, 1986;Nilius, 1988;Moorman et al, 1990;Zhou et al, 199 1) are somewhat similar to those found for N-type Ca2+ channels (Plummer and Hess,199 1; see Different Kinetic Patterns, above).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Modal changes in both activation and inactivation kinetics have been reported. The inactivation gating modes found for Na channels (Patlak and Ortiz, 1986;Nilius, 1988;Moorman et al, 1990;Zhou et al, 199 1) are somewhat similar to those found for N-type Ca2+ channels (Plummer and Hess,199 1; see Different Kinetic Patterns, above).…”
Section: Discussionsupporting
confidence: 61%
“…These include ligand-gated channels for glutamate (Patlak et al, 1979) and GABA (Macdonald and Twyman, 199 1) as well as voltage-gated channels such as Na channels (Patlak and Ortiz, 1986;Nilius, 1988;Moorman et al, 1990;Zhou et al, 1991) and Ca*+-activated K+ channels (Moczydlowski and Latorre, 1983;McManus and Magleby, 1988). Modal changes in both activation and inactivation kinetics have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears to be different from the process underlying the SyPP. Alternatively, the situation may be similar to cardiac and skeletal muscle where a slow sodium current has been attributed to multiple re-openings of single classical sodium channels (Patlak & Ortiz, 1985Nilius, 1988;Josephson & Sperelakis, 1989). A third alternative G.-Y.…”
Section: Synaptic Prepotentials Elicited By Proximal and Distal Inputsmentioning
confidence: 99%
“…It is noteworthy that most experiments on Na ϩ current properties in central neurons have been performed under conditions which might limit the exposure of channels to endogenous cytoplasmic factors. Often, Na ϩ channels are recorded in excised patches, which distances them from the cytoplasm and alters their kinetic and inactivation properties (12,13). Most cell-attached recordings have been from isolated cell preparations, which might be depleted of molecules released from nearby neurons and glia.…”
mentioning
confidence: 99%